Entre falas e silêncios : a (in)visibilidade da temática do suicídio em sites de notícias do Vale do Araguaia - MT - Franco, Talita Furtado de Queiroz (2022)
Suicide is one of the leading causes of death in the world. Each year, about 800,000 people take their own lives, and an even greater number of individuals attempt suicide. This qualitative work aims to apprehend the meanings of the reverberation of the suicide event on websites in the cities of Água Boa, Nova Xavantina and Barra do Garças (Água Boa News, Interativa FM, Nx1 and Araguaia Notícia), located in the region of Vale do Araguaia, northeast of the state of Mato Grosso, with populations between 20 and 60 thousand inhabitants. The research was developed with the following questions: how do websites organize news about suicide and how do they appeal to us? The choice of this object was due to the fact that these sites are the most representative and with the most views in the region. Each suicide is a tragedy that affects families, communities and entire countries, has lasting effects on the people left behind, and, in inland cities such as those analyzed, the cases have some particularities such as the proximity of the subjects involved, where “ Everyone know each other". Suicide is little explored in the main writing manuals in the country, the lack of guidance on the subject may be a reflection of the cultural taboo and stigmas surrounding the topic, and even in the codes of ethics that should guide practice and deontology. journalism, the subject is little discussed. However, what was observed, in the analyzed sites, that cases of suicide are widely explored when it comes to residents of the region. The theoretical axis constitutes the relational idea of communication by Vera França, the relational paradigm understands communication as a process and with basic dynamics: the interlocution between subjects — the symbolic materiality (the discourse) and the sociocultural context. To contextualize, Louis Quéré and Vera França's idea of event are facts that happen to someone; that cause disruption and disorganization, that introduce a difference. They make us think, arouse meanings and make us act (they have a pragmatic dimension). There is an emphasis on the double life of the event, the moment when it gains a symbolic existence and turns into discourse, the spaces where events are reflected, in this case, the media. In the case of suicide, death by its own action is an existential event, the second life of the event is of the order of culture: what makes one speak, MESTRADO - Folha de Aprovação 5033613 SEI 23108.058570/2022-18 / pg. viiiattribute meanings and values. The operating concepts are Erving Goffman's Framing and Alfred Schutz's Typifications, which significantly contribute as a theoretical-methodological framework for the analysis of the empirical object of this research based on the news framing. It was observed, at the end of this work, that all the subjects, therefore, did not present an in-depth debate on the subject, only vague appealing ramblings loaded with value judgments, stigmas and taboos, without the commitment to seek prevention according to the molds of organizations of health or try to broaden the understanding of the sociocultural context of the gesture. In summary, an observation that is reiterated pertinent for being an idea that crosses this study: the invisibility addressed situates the fact that the suicide that is seen as news in the media has a veil of invisibility.